Effects of different vaccine combinations against Mycoplasma gallisepticum on the internal egg and eggshell characteristics of commercial layer chickens1, 2, 3. (19th February 2015) - Jacob, R.; Branton, S. L.; Evans, J. D.; Leigh, S. A.; Peebles, E. D.
Abstract : Live F-strain Mycoplasma gallisepticum (FMG) vaccines are presently being used to help control field-strain MG outbreaks. However, they may exert some adverse effects on egg production. Live strains of MG of lesser virulence as well as killed vaccines have little or no effect on egg production, but afford lower levels of protection. This has led to research investigating their use in combination with a subsequent overlay vaccination of FMG given later in the production cycle. In the present study, 2 trials were conducted to investigate the effects of prelay vaccinations of live and killed MG vaccines or their combination, in conjunction with an FMG vaccine overlay after peak production, on the egg characteristics of commercial layers. The following vaccination treatments were administered at 10 wk of age (woa): 1) unvaccinated (Control), 2) MG–Bacterin (MGBac) vaccine, 3) ts-11 strain MG (ts11MG) vaccine, and 4) MGBac and ts11MG combination (MGBac + ts11MG). At 45 woa, half of the birds were overlaid with an FMG vaccine. In each trial, internal egg and eggshell parameters including egg weight (EW), Haugh unit score (HU), eggshell breaking strength (EBS), percentage yolk weight (PYW), percentage albumen weight (PAW), percentage eggshell weight (PSW), eggshell weight per unit surface area (SWUSA), percentage yolk moisture (PYM), and percent total lipids (PYL) were determined at various time periods between 21 and 52 woa. At 28 woa, SWUSA was lower in the ts11MG and MGBac + ts11MG groups compared to the Control group. Conversely, at 43 woa, SWUSA was higher in the ts11MG than in the MGBac group. Between 23 and 43 woa, PYL was higher in the MGBac and ts11MG groups in comparison to the Control group. In conclusion, vaccination with MGBac alone or in combination with ts11MG at 10 woa with or without an FMG vaccine overlay at 45 woa does not adversely affect the internal egg or eggshell quality of commercial layers throughout lay.